Association of comprehensiveness of antiretroviral care and detectable HIV viral load suppression among pregnant and postpartum women in the Democratic Republic of the Congo: a cross-sectional study - Boisson-Walsh, Alix; Ravelomanana, Noro L. R.; Tabala, Martine; Malongo, Fathy; Kawende, Bienvenu; Babakazo, Pélagie; Yotebieng, Marcel (Frontiers in Global Women's Health, 2024)
Introduction Worldwide, over two-thirds of people living with HIV are on antiretroviral therapy (ART). Despite increased ART access, high virological suppression prevalence remains out of reach. Few studies consider the quality of ART services and their impact on recipients' viral suppression. We assessed the association between ART service readiness and HIV viral load suppression among pregnant and breastfeeding women living with HIV (WLH) receiving ART in maternal and child health (MCH) clinics in Kinshasa, Democratic Republic of Congo. Methods We performed a cross-sectional analysis leveraging data from a continuous quality improvement intervention on WLH's long-term ART outcomes. From November 2016 to May 2020, we enrolled WLH from the three largest clinics in each of Kinshasa'Łs 35 health zones. We measured clinic's readiness using three WHO-identified ART care quality indicators: relevant guidelines in ART service area, stocks of essential ART medicines, and relevant staff training in ≥24 months, scoring clinics 0-3 based on observed indicators. We defined viral load suppression as ≤1,000 cp/ml. Multilevel mixed-effect logistic models were used to estimate prevalence odds ratios (ORs) measuring the strength of the association between ART service readiness and viral suppression. Results Of 2,295 WLH, only 1.9% received care from a clinic with a score of 3, 24.1% received care from a 0-scoring clinic, and overall, 66.5% achieved virologically suppression. Suppression increased from 65% among WLH receiving care in 0-scoring clinics to 66.9% in 1-scoring clinics, 65.8% in 2-scoring clinics, and 76.1% in 3-scoring clinics. We did not observe a statistically significant association between ART service readiness score and increased viral suppression prevalence, however we did find associations between other factors, such as the location of the health center and pharmacist availability with suppressed viral load. Discussion A lack of comprehensive ART care underscores the need for enhanced structural and organizational support to improve virological suppression and overall health outcomes for women living with HIV..